Systematic position of Phyllanthus talbotii (Phyllanthaceae), a critically endangered species of Western Ghats, India - Naik, S. S.; Pagare, R. S.; Krishnan, S.; Janarthanam, M. K. (Rheedea, 2013)
Phyllanthus talbotii Sedgw. (Phyllanthaceae) is endemic to Western Ghats regions of Goa and Karnataka, India and is critically endangered. For a long time, it was known only from the type collection and a subsequent untraceable collection and hence taxonomically not fully understood, though a recent treatment has placed it under subgenus Eriococcus. In the present study, attempts were made to confirm its position using morphological characters and sequences of nuclear internal transcribed spacer (ITS) of nuclear ribosomal DNA (nrDNA) and chloroplast mat K genes. Results from ITS and mat K phylogenetic analyses supported its placement in subgenus Eriococcus.